al-Qalaq wa Aliyat ad-Difa' an-Nafsi fi Syakhsiyah "Ana" fi al-Qisshah al-Qashirah "Wajhul Haqiqah" li Taufiq al- Hakim - Hanifah Mu'izah; Yeni Ratna Yuningsih; Ulil Abshar; Yani'ah Wardani; Arif Albanna Tama Sormin (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
Abstract: This study examines the forms of anxiety and defense mechanisms experienced by the character "I" in the short story Wajh al-?aq?qah by Taufiq al-Hakim using a literary psychology approach, specifically Sigmund Freud's psychoanalytic theory. The focus of this Research is on how anxiety and defense mechanisms emerge and play a role in shaping the inner dynamics of the main character. The method used is textual analysis by closely examining the narrative and dialogues that reflect the character's psychological conflicts. The findings reveal that the character "I" experiences three types of anxiety: realistic anxiety (identified in 5 sentences), neurotic anxiety (7 sentences), and moral anxiety (11 sentences). Furthermore, seven out of nine defense mechanisms proposed by Freud were found: repression (3 sentences), sublimation (6 sentences), projection (2 sentences), displacement (1 sentence), rationalization (5 sentences), reaction formation (2 sentences), and fantasy (2 sentences). Overall, the study shows that the character "I" undergoes a complex and layered internal struggle, as reflected through dominant forms of anxiety and a variety of defense strategies employed to maintain psychological stability.